The Mesolithic settlement and economy in the Lake Gościąż area - Pelisiak, Andrzej; Rybicka, Małgorzata (the Authors, 2020)
Lake Gościąż is located in a Gostinińskie Lake District (Central Poland). It contains long and good preserved continuous sequence of the annually laminated lake sediments spanning from the end of the last glaciation to contemporary times. They offer unique opportunities for investigating changes in the environment and human activity in the vicinity of the lakes. This paper is focused on correlation of palynological indicators of activity of the Mesolithic people with the picture of settlement in the region. Another problem discussed there question of reliability of palynological data, and therefore their usefulness for studies on settlement and economy.
Keywords: annually laminated lake sediments; palynology; Mesolithic; Gościąż lake; environmental changes